PHP 7 real world application development : use new features of PHP 7 to solve practical, real-world problems faced by PHP developers like yourself every day : a course in three modules - Bierer, Doug; Hussain, Altaf; Jones, Paul (Packt Publishing, 2016)
Use new features of PHP 7 to solve practical, real-world problems faced by PHP developers like yourself every day. About This Book This course covers the new features of version 7.x, best practices for server-side programming, and MVC frameworks Leverage the potential of PHP for server-side programming, memory management, and Object-Oriented Programming to improve your programming productivity This course also illustrates the development of a complete modular application using PHP 7 in detail Who This Book Is For If you are an aspiring web developer, mobile developer, or back-end programmer, who has basic experience in PHP programming and wants to develop performance-critical applications, then this course is for you. It will take your PHP programming skills to next level. What You Will Learn Solve practical real-world programming problems using PHP 7 Discover where and when PHP 5 code needs to be re-written to avoid backwards-compatibility breaks Use advanced PHP 7 features such as the Abstract Syntax Tree, Uniform Variable Syntax, Scalar Type Hints, Generator Delegation, Anonymous Classes, and the Context Sensitive Lexer Set up a high performance development and production environment for PHP 7 Discover new OOP features in PHP 7 to achieve high performance Discover the new features of PHP 7 that are relevant to modular application development Explore the ins and outs of the Symfony framework Build a set of modules based on the Symfony framework that comprise a simple web shop app In Detail PHP is a great language for developing web applications. It is essentially a server-side scripting language. PHP 7 is the latest version, providing major backward-compatibility breaks and focusing on improved performance and speed. This course follows a learning path which is divided into three modules. Each module is a mini course in its own right, taking your basic PHP programing skills to the next level by showing you intermediate to advanced PHP techniques with a focus on PHP 7. This way, get you equipped with the tools and skills required to develop professional and efficient applications for your websites and enterprises. The first module of the book is a programming cookbook that consists over 80 recipes! Each recipe is designed to solve practical, real-world problems faced by PHP developers like yourself every day. This course also covers new ways of writing PHP code made possible only in version 7. The second module of the course is designed to im...
Authors: Doug Bierer, Altaf Hussain, Paul Jones. Cf. Credits page. - Includes bibliographical references and index. - Online resource; title from title page (Safari, viewed November 3, 2016)
Keywords: PHP (Computer program language); Web site development; PHP (Langage de programmation); Sites Web; Développement; COMPUTERS; Programming Languages; SQL